Answers:
![f(g(x)) = √(x^2+5)+5\\\\g(f(x)) = x+30+10√(x-1)](https://img.qammunity.org/2021/formulas/mathematics/college/sfpq8v8nxfqbl200e5cq3qbcl59rg76fqk.png)
================================================
Work Shown:
Part 1
![f(x) = √(x-1)+5\\\\f(g(x)) = √(g(x)-1)+5\\\\f(g(x)) = √(x^2+6-1)+5\\\\f(g(x)) = √(x^2+5)+5\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/3upkk05209mwqrdwy113wktozwqhlkp55y.png)
Notice how I replaced every x with g(x) in step 2. Then I plugged in g(x) = x^2+6 and simplified.
------------------
Part 2
![g(x) = x^2+6\\\\g(f(x)) = \left(f(x)\right)^2+6\\\\g(f(x)) = \left(√(x-1)+5\right)^2+6\\\\g(f(x)) = \left(√(x-1)\right)^2+2*5*√(x-1)+\left(5\right)^2+6\\\\g(f(x)) = x-1+10√(x-1)+25+6\\\\g(f(x)) = x+30+10√(x-1)\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/vmj6t8yv203esrcegu7vt7ibe7weajhbof.png)
In step 4, I used the rule (a+b)^2 = a^2+2ab+b^2
In this case, a = sqrt(x-1) and b = 5.
You could also use the box method as a visual way to expand out
![\left(√(x-1)+5\right)^2](https://img.qammunity.org/2021/formulas/mathematics/college/lo06br1iifh5s3kq3u1hn6kok08nhiyin6.png)